No effect of glycemic index of pre-exercise meals with carbohydrate intake during exercise - Burke, L. M.; Claassen, A.; Hawley, J. A.; Noakes, T. D. (Medicine & Science in Sports & Exercise, 1998)
The effects of the glycemic index of pre-exercise meals on metabolism and cycling performance when carbohydrate (CHO) was ingested throughout exercise were investigated. Well-trained cyclists (N = 6) performed three trials consisting of 2-hours cycling at 70% of VO2max followed by a performance ride of 300 kJ. Meals were fed two hours before exercise and consisted of 2 gm/kg of CHO of either high glycemic index (potato) or low glycemic index (pasta), or a placebo. During exercise, Ss ingested a total of 24 ml/kg of a glucose solution. Pre-exercise differences were noted in glucose, insulin, and free-fatty acid between trials. There were no differences in total CHO oxidation nor oxidation of ingested CHO. There no differences in time to complete the performance ride. It was concluded that consumption of large amounts of CHO during a performance offsets any pre-exercise differences in CHO related factors and their potential effects on metabolism and cycling performance.